Eight‐Electron Redox Cyclohexanehexone Anode for High‐Rate High‐Capacity Lithium Storage. Issue 30 (19th June 2022) - Li, Sha; Lin, Jiande; Zhang, Yimiao; Zhang, Shilin; Jiang, Tao; Hu, Zhongli; Liu, Junjie; Wu, De‐Yin; Zhang, Li; Tian, Zhongqun
Abstract: Replacing inorganic anodes with organic electrode materials is an attractive direction for future green Li‐ion batteries (LIBs). Carbonyl compounds are being explored as leading anode candidates for organic LIBs. In particular, cyclohexanehexanone (C6 O6 ), as a perfect structure composed entirely of six CO groups, can theoretically contribute to the most reactive sites and the highest specific capacity, but has not been used as an anode material so far owing to its high solubility in carbonate‐based electrolytes and extremely low electronic conductivity. Herein, C6 O6 is first revealed as an ultra‐high capacity and high‐rate anode material through a total eight‐electron redox electrochemical process by effectively constructing an insoluble and highly conductive C6 O6 ‐polymeric binder‐carbon network architecture. Experimental characterizations combined with first‐principles calculations elucidate that CO bonds in C6 O6 can be lithiated to Li + enolate (Li6 C6 O6 ) through a reversible six‐Li‐ion electrochemical process and further converted to Li8 C6 O6 dimers via a reversible two‐electron pseudocapacitive Li + intercalation reaction. As such, the C6 O6 anode shows an ultrahigh capacity of up to 1404 mAh g −1 at 200 mA g −1 and an extraordinary high‐rate durability (814 mAh g −1 after 700 cycles at 5.0 A g− 1 ). A 4.3 V high energy/power density Li‐ion hybrid electrochemical capacitor based on the C6 O6 anode is thus derived. Abstract : Cyclohexanehexone (C6 O6 ) composed entirely of CO groups is first revealed as an ultra‐high capacity and high‐rate anode material for lithium‐ion batteries. Experimental characterizations combined with first‐principles calculations elucidate that CO bonds in C6 O6 can be lithiated to Li + enolate (Li6 C6 O6 ) through a reversible six‐Li‐ion electrochemical process and further converted to Li8 C6 O6 dimers via a reversible two‐electron pseudocapacitive Li + intercalation reaction.